Analisa Ketahanan Benturan Struktur Bumper Berbasis Material Komposit Hibrida Menggunakan Metode Finite Element Area (FEA) - Adit Aryadi; Karnowo (Universitas Muhammadiyah Surabaya, 2026)
Traffic accidents, especially frontal collisions, often cause severe damage to the front structure of vehicles. Bumpers play a crucial role in absorbing impact energy and reducing structural damage. This study analyzes the impact resistance of bumper structures using Acrylonitrile Butadiene Styrene (ABS), Jute-Flax (JR) hybrid composites, and Coconut Shell Particle Polypropylene (PPCSP) composites through Finite Element Analysis (FEA). The bumper geometry was designed in SolidWorks and simulated in ANSYS Workbench using explicit dynamics method. Three collision velocities were applied: 11110 mm/s, 15610 mm/s, and 22220 mm/s. The performance was evaluated based on total deformation, von Mises stress, and safety factor. The results showed that the JR composite achieved the lowest deformation and the highest safety factor, while the PPCSP exhibited lower stress values at higher speeds. Compared with ABS, both composites showed better structural performance under dynamic loads. These findings suggest that hybrid natural fiber composites are a promising alternative for automotive bumper applications. Keywords: bumper, explicit dynamics, finite element analysis, hybrid composite, frontal crash